Efficacy of the acupressure wrist-ankle strap in mild insomnia patients with anxiety disorders: study protocol for a randomized controlled trial - Ying Yuan (BMC, 2021)
Abstract Background Insomnia is very common in current society, and patients are often accompanied by a certain degree of anxiety, depression, etc. Recent studies have found that the hypothalamic-pituitary-adrenal (HPA) axis excitement-inhibition state is an important indicator of sleep quality. Wrist-ankle acupuncture (WAA) is safe and effective for insomnia. Based on WAA theory, the acupressure wrist-ankle straps are portable WAA point compression straps that can treat diseases by automatically applying pressure to the treatment location and being operated by patients themselves. We design this trial to evaluate the clinical effect of the acupressure wrist-ankle strap in the treatment of mild insomnia patients with anxiety disorders. Methods/design This trial is a parallel-design, patients-assessor blinded, randomized, sham-controlled. In total, 114 patients diagnosed with mild insomnia and anxiety disorders will be randomly assigned into two groups, the acupressure wrist-ankle strap group or the non-acupressure wrist-ankle strap group; they will receive treatments for eight weeks with five sessions each week. Rating scales, sleep monitors, and laboratory tests will be used to observe the clinical effect. From the perspective of the circadian secretion of peripheral blood-related hormones in the hypothalamic-pituitary-adrenal (HPA) axis, the possible mechanism of acupressure wrist-ankle straps for treating insomnia is studied. Discussion The results of this study will confirm the efficacy of acupressure wrist-ankle strap in treating mild insomnia patients with anxiety disorder and whether its mechanism is related to the HPA axis. The acupressure wrist-ankle strap may become a pure physical, no side effect treatment of mild insomnia. Trial registration Chinese Clinical Trial Registry ChiCTR2000039352 . Registered on 24 October 2020.